1986
DOI: 10.1093/infdis/154.6.990
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk of Hepatitis B from Institutionalized Mentally Retarded HBsAg Carriers: A Prospective Study

Abstract: In an institution for the mentally retarded, a total of 13 (2.4%) susceptible employees seroconverted for hepatitis B during 539 person-years. Two of them developed acute hepatitis B; the cost of their medical care and temporary disability was $7,772. Eleven seroconverters had no elevation of serum alanine aminotransferase, and all seroconverters recovered without chronic sequelae. Nine converters acquired antibody to HBsAg alone; three of these had no client contact. Difficulty in identifying nonoccupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Most studies found a higher proportion of post-infection conditions (anti-HBc positive) in mentally impaired residents compared to the general population [6][7][8][9][10] . Increased HBV seroconversion rates among teachers have also been described previously, assuming the presence of HBV carriers among pupils 2,3 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Most studies found a higher proportion of post-infection conditions (anti-HBc positive) in mentally impaired residents compared to the general population [6][7][8][9][10] . Increased HBV seroconversion rates among teachers have also been described previously, assuming the presence of HBV carriers among pupils 2,3 .…”
Section: Discussionsupporting
confidence: 66%
“…Available and effective vaccines can prevent hepatitis A (HAV) and hepatitis B (HBV) infections 1 . In advance, various studies have described an increased prevalence of HBV among pupils and teachers in special schools for handicapped children and an increased seroconversion rate compared to the general population [2][3][4] .…”
mentioning
confidence: 99%
“…Most studies found a higher proportion of post-infection conditions (anti-HBc positive) in mentally impaired residents compared to the general population (6-10). Increased HBV seroconversion rates among teachers have also been described previously, assuming the presence of HBV carriers among pupils (3,2).…”
Section: Hbv Hazards In the Workplacesupporting
confidence: 65%
“…Available and effective vaccines can prevent HAV and HBV infections (1). In advance, various studies have described an increased prevalence of HBV among pupils and teachers in special schools for handicapped children and an increased seroconversion rate compared to the general population (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Unless adequate preventive measures are taken, their safety and health could be severely jeopardized (9). Such prevention requires thorough knowledge of the risks and practical measures which can be taken on time (8,(10)(11). Therefore, everyone should be familiarized with universal precautions at work, as defined by the Centre for Disease Control to prevent the transmission of HBV, hepatitis C virus, human immunodeficiency virus (HIV) and blood-borne infections (12).…”
Section: Introductionmentioning
confidence: 99%